New approaches to the creation of high-performance radiation detectors for concentrator solar modules - Борщев, В.Н.; Листратенко, А.М.; Проценко, М.А.; Тымчук, И.Т.; Кравченко, А.В.; Слипченко, Н.И. (Radiotekhnika, 2019)
Current state and trends in the development of solar photovoltaics, including technology of concentrator solar modules on Fresnel lenses and mirror concentrators, are considered. New approaches to creation of high-performance receivers of concentrated solar radiation based on aluminum-polyimide Chip-On-Flex (COF) assembly technology and gallium arsenide solar cells with efficiency of 46-48% have been proposed. Experimental samples of innovative solar radiation receivers for point concentrator modules on Fresnel lenses were manufactured and investigated.